REPRESENTASI GESTUR BAHASA ISYARAT DALAM FILM MOVIE A SILENT VOICE TERHADAP POLA KOMUNIKASI ANTAR PRIBADI: Analisis gestur tangan bahasa isyarat film A Silent Voice - Widya Kanti Puspita; Yatno, Tri; Sujiono (LPPM Stikosa - AWS, 2025)
A Silent Voice is one of the films that addresses the issue of deafness, focusing on interpersonal communication patterns. The purpose of this study is to identify the types of hand gestures and describe the meanings of sign language hand gestures in the film A Silent Voice. Through semiotic analysis, this study seeks to uncover how the meanings conveyed through hand gestures in the film can influence interpersonal communication and shape society's perspective on the deaf community. The study employs a descriptive qualitative method through symbolic analysis. The research was conducted from January 2025 to June 2025. The data and data source are the film A Silent Voice. Data validity testing techniques in this study use triangulation. The triangulation used in this study is source triangulation and technique triangulation. The data analysis technique used in this study is data analysis referring to Miles & Habermint. The analysis process consists of three concurrent activities: data reduction, data presentation, and conclusion drawing/verification. The findings of this study identified five types of sign language hand gestures: friendship hand gestures, question hand gestures, thank you hand gestures, farewell hand gestures, and apology hand gestures. These hand gestures impact interpersonal communication patterns, as demonstrated through the sign language hand gestures in the film A Silent Voice, which are capable of building social interaction and more effective communication processes.